Special economic zones and impacts on land resources and socio-economic implications - Dhar, T.N. (2011)
Development and economic growth traverse a common course where progressively people move away from agriculture towards industry and urban areas. Growth in industrial activity is the motivation behind this shift, yielding people and land for non-farm activities. India is no exception to this phenomenon and the debate of agriculture versus industrial-focused special economic zones (SEZs) is getting intensified. Be it SEZs or increasing urbanisation, there is no denying the fact that change has arrived and appropriate policies and strategies need to be put in place to grab the advantages of globalised industrial activity without compromising on the food and nutrition security. Sacrificing agricultural land for setting up SEs may create obstacles for the social and economic development, particularly in rural areas. - Reproduced.
Keywords: Land resources; Economic zones